1987
DOI: 10.1042/bj2480511
|View full text |Cite
|
Sign up to set email alerts
|

Action of long-chain fatty acids in vitro on Ca2+-stimulatable, Mg2+-dependent ATPase activity in human red cell membranes

Abstract: Human red cell membrane Ca2+-stimulatable, Mg2+-dependent adenosine triphosphatase (Ca2+-ATPase) activity and its response to thyroid hormone have been studied following exposure of membranes in vitro to specific long-chain fatty acids. Basal enzyme activity (no added thyroid hormone) was significantly decreased by additions of 10(-9)-10(-4) M-stearic (18:0) and oleic (18:1 cis-9) acids. Methyl oleate and elaidic (18:1 trans-9), palmitic (16:0) and lauric (12:0) acids at 10(-6) and 10(-4) M were not inhibitory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 31 publications
2
10
0
Order By: Relevance
“…In general it is known that any factor which influences the composition of the cell membrane or the calcium transporters will result in excessive altered calcium fluxes with subsequent disturbances in the intracellular calcium status (Farber, 1981; Duncan, 1991; Matthews et al ., 1993; Trump & Berezesky, 1995). In chronic renal failure, factors that may potentially influence the intracellular calcium status include the reported abnormal parathyroid hormone levels (Alexiewicz et al ., 1990; Massry & Smogorzewski, 1994), oxidative damage to cell membranes (Luciak & Trznadel, 1991; Taccone‐Gallucci et al ., 1992; Lin et al ., 1996), decreased antioxidant activity (Nagase et al ., 1996), deranged calcium‐ATPase function (Davis et al ., 1987; Zidek et al ., 1992; Taffet et al ., 1993; Takahashi & Yamaguchi, 1994; Starling et al ., 1995; Lindner et al ., 1997), deranged sodium/potassium‐ATPase function (Islam et al ., 1989) and any calcium channel agonist or antagonist present in unphysiological proportions, including calcium channel blockers.…”
Section: Introductionmentioning
confidence: 99%
“…In general it is known that any factor which influences the composition of the cell membrane or the calcium transporters will result in excessive altered calcium fluxes with subsequent disturbances in the intracellular calcium status (Farber, 1981; Duncan, 1991; Matthews et al ., 1993; Trump & Berezesky, 1995). In chronic renal failure, factors that may potentially influence the intracellular calcium status include the reported abnormal parathyroid hormone levels (Alexiewicz et al ., 1990; Massry & Smogorzewski, 1994), oxidative damage to cell membranes (Luciak & Trznadel, 1991; Taccone‐Gallucci et al ., 1992; Lin et al ., 1996), decreased antioxidant activity (Nagase et al ., 1996), deranged calcium‐ATPase function (Davis et al ., 1987; Zidek et al ., 1992; Taffet et al ., 1993; Takahashi & Yamaguchi, 1994; Starling et al ., 1995; Lindner et al ., 1997), deranged sodium/potassium‐ATPase function (Islam et al ., 1989) and any calcium channel agonist or antagonist present in unphysiological proportions, including calcium channel blockers.…”
Section: Introductionmentioning
confidence: 99%
“…60 % and 44 % as active as all-trans retinoic acid) at a concentration of 10-8 M. We have previously reported that retinol and retinal do not inhibit Ca2+-ATPase activity [14]. Although some long-chain fatty acids, such as oleic (C,8 l) and stearic (C18:0) acids inhibit Ca2+-ATPase activity [12], two short-chain fatty acids, sorbic (C6:2) and tiglic (branched C6:1) acids, were without effect on Ca2+-ATPase (results not shown).…”
Section: Ca2+-atpase Activitymentioning
confidence: 94%
“…Among these calmodulin inhibitors are N-(6-aminohexyl)-5-chloronaphthalene- 1-sulphonamide (W-7) [6], calmidazolium [7], phenothiazines such as trifluoperazine [8], Ca2+ channel blockers [9,10], and the antiarrhythmic agent amiodarone [11]. Several fatty acids, including oleic acid [12], also inhibit human erythrocyte membrane Ca21-ATPase activity. The calmodulin antagonism by fatty acids apparently does not depend upon direct interaction of fatty acids with the Ca2+-binding protein, but rather upon their interaction with the plasma membrane at or near the calmodulin-binding site [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Long-chain fatty acids that are routinely present in plasma of normal individuals were shown to have cytotoxic effects at high concentrations, impair ATP generation, uncouple OXPHOS, inhibit the respiratory chain, depolarize mitochondria by their protonophoric properties, induce oxidative stress, and have permeability transition. [44][45][46][47][48][49] Medium-chain fatty acid effects on mitochondrial functions are less studied, but may similarly affect mitochondrial respiration and disturb the translocation of ADP in mitochondria. 50 Therefore, it is feasible that the fatty acids that accumulate in tissues of patients with MCAD and LCHAD deficiencies (Table 3) may similarly induce cellular toxicity.…”
Section: Disruption Of Mitochondrial Homeostasis In Mcad and Lchad Dementioning
confidence: 99%